A Giant Left Atrium due to Rheumatic Mitral Regurgitation, Outcome after Left Atrial Reduction Surgey with Mitral Valve Replacement - Ahmed, Istiaq; Hossain, Sorower; Paul, Ankan Kumar (University Heart Journal, 2018)
A trans-thoracic echocardiography and chest radiograph of a 26 year old lady diagnosed as rheumatic mitral regurgitation with atrial fibrillation revealed a giant left atrium of 10.9 cm size with symptoms of dyspnoea and palpitation. The patient was treated with left atrial size reduction along with mitral valve replacement surgery and showed an excellent and quick recovery with total disappearance of symptoms and restoration of sinus rhythm only within few days. University Heart Journal Vol. 14, No. 1, Jan 2018; 42-44